A new species of Pachytrocha Kent, 1882 (Ciliophora, Peritrichia: Vaginicolidae) - Boshko, Elena G.; Konstantynenko, Lyudmila A. (Zootaxa, 2009)
The peritrich ciliate Pachytrocha zhytomirensis n. sp. is described from the sewage treatment system of Zhytomir (Ukraine). The new species is characterized by an elongate, subgeniculate lorica sheltering a single zooid with an annular ridge and a peristomial lip thickened noticeably near the entrance to the infundibulum. When contracting, the upper part of the cell bends toward the wall of the lorica and the inflated edge of the peristomial lip covers the body. The macronucleus is ribbon-like and oriented parallel to the longitudinal axis of the cell. Cothurnia asymmetrica Sommer, 1951 is recognized as a synonym of Pachytrocha cothurnoides Kent, 1882.